Stimuli-Responsive Gels - Dirk Kuckling (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [Although the technological and scientific importance of functional polymers have been well established over the last few decades, the most recent focus that has attracted much attention concerns stimuli-responsive polymer gels. These materials are of particular interest due to their abilities to respond to internal and/or external chemo-physical stimuli. Aside from the scientific challenges of designing stimuli-responsive polymer gels, the main technological interests concern numerous applications, ranging from catalysis in microsystem technology and chemo-mechanical actuators to sensors. This Special Issue includes seventeen papers covering a wide range of subjects including thermo- and pH-responsive hydrogels, functionalized materials, supramolecular stimuli-responsive structures, composite hydrogels, sensors, and biomedical applications. Together, these contributions not only provide an excellent overview of the current state-of-the-art in the field but also point out exciting challenges and opportunities for future work. In a number of reviews the most recent findings on "Stimuli-Responsive Gels" are compiled in this book supplemented by original contributions.